The Urgency of Restorative Justice Principles in Law Enforcement Efforts against Defamation Crimes through Social Media Twitter in Indonesia - Retno Hariati; Abdul Kholiq (Dinasti Research, 2024)
This study seeks to ascertain the efforts to enforce restorative justice especially through defamation crimes on social media twitter based on positive law and inhibiting and supporting factors in the enforcement of restorative justice in criminal defamation on twitter social media in Indonesia. The method being used for this research is normative and the data collection method to be used is Library Research. The results of this study indicate that the National Police Chief Regulation No. 8 of 2021 provides a legal basis for the integration of restorative justice in police actions against crimes related to information and electronic transactions. The Indonesian National Police responded to the growing legal needs by developing new ideas through the National Police Chief Circular Letter No. 08/2018 and SE/2/II/2021 on Ethical Cultural Awareness in Digital Space. The obstacles mainly arise from the lack of regulations, especially in the ITE Law which has not specifically accommodated restorative justice as a solution in cases of criminal information and electronic transactions. Besides the fact it requires a mutual agreement between the victim and the perpetrator, restorative justice also cannot be applied if the perpetrator uses an anonymous account that cannot be identified.